2014
DOI: 10.17723/aarc.77.2.2458080u50422715
|View full text |Cite
|
Sign up to set email alerts
|

The Northwest Archivists Mentoring Program: A Case Study

Abstract: The Northwest Archivists (NWA), a regional archival association in the Pacific Northwest, established a formal mentoring program in 2007. A pilot phase of the program ran for 2 years and included both formative and summative assessments from participants. This case study documents NWA's experiences designing and managing a mentoring program within a volunteer-run professional association, reflects on the program's successes and challenges, and recommends areas for future investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…45 A second study, centering on associational mentoring among members of the Northwest Archivists (NWA), discerned that three-quarters of mentors and 70% of mentees fully or generally agreed that their match proved salutary. 46 As an ancillary benefit, the vast majority (90%) of mentees said that participating in the program improved their opinions of NWA. 47 A third study (a meta-analysis that included both academic and professional settings) found mentoring significantly related to numerous positive outcomes, from attitudinal and interpersonal to motivational, from health-related to career outcomes.…”
Section: Mentoringmentioning
confidence: 99%
“…45 A second study, centering on associational mentoring among members of the Northwest Archivists (NWA), discerned that three-quarters of mentors and 70% of mentees fully or generally agreed that their match proved salutary. 46 As an ancillary benefit, the vast majority (90%) of mentees said that participating in the program improved their opinions of NWA. 47 A third study (a meta-analysis that included both academic and professional settings) found mentoring significantly related to numerous positive outcomes, from attitudinal and interpersonal to motivational, from health-related to career outcomes.…”
Section: Mentoringmentioning
confidence: 99%